Navigating Distance and Traditional Higher Education: Online faculty experiences - Yick, Alice G.; Patrick, Pam; Costin, Amanda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The academic culture of higher educational institutions is characterized by specific pedagogical philosophies, assumptions about rewards and incentives, and values about how teaching is delivered. In many academic settings, however, the field of distance education has been viewed as holding marginal status. Consequently, the goal of this qualitative study was to explore faculty members’ experiences in a distance education, online university while simultaneously navigating within a traditional environment of higher education. A total of 28 faculty members participated in a threaded, asynchronous discussion board that resembled a focus group. Participants discussed perceptions about online teaching, working in an institution without a traditional tenure system, and the role of research in distance education. Findings indicated that online teaching is still regarded as less credible; however, participants also noted how this perception is gradually changing. Several benchmarks of legitimacy were identified for online universities to adopt in order to be viewed as credible. The issue of tenure still remains highly debated, although some faculty felt that tenure will be less crucial in the future. Finally, recommendations regarding attitudinal shifts within academic circles are described with particular attention to professional practice, program development, and policy decision-making in academia.